Protein S-palmitoylation regulates the virulence of plant pathogenic fungi - Mengmeng Guo; Leeza Tariq; Fengming Song (mBio)
ABSTRACT Protein S-palmitoylation, a universal posttranslational modification catalyzed by a specific group of palmitoyltransferases, plays crucial roles in diverse biological processes across organisms by modulating protein functions. However, its roles in the virulence of plant pathogenic fungi remain underexplored. In a recent study, Y. Duan, P. Li, D. Zhang, L. Wang, et al. (mBio 15:e02704-24, 2024, https://doi.org/10.1128/mbio.02704-24) reported that the palmitoyltransferases UvPfa3 and UvPfa4 regulate the virulence of the rice false smut pathogen Ustilaginoidea virens. Through comprehensive characterization of S-palmitoylation sites, they revealed that S-palmitoylated proteins in U. virens are enriched in mitogen-activated protein (MAP) kinase and autophagy pathways, with MAP kinase UvSlt2 being a key target of UvPfa4-mediated S-palmitoylation. Further investigation demonstrated that S-palmitoylation of UvSlt2 is critical for its kinase activity, substrate interaction ability, and virulence function in U. virens. These findings reveal UvPfa4-mediated S-palmitoylation as a vital regulatory mechanism in U. virens virulence, highlighting the importance of protein S-palmitoylation in the pathogenicity of plant pathogenic fungi.